Self-management education programme on functional mobility for knee osteoarthritis in older adults. - Kamsan, Siti Salwana; Singh, Devinder Kaur Ajit; Kumar, Saravana; Tan, Maw Pin (2021)
Introduction Knee osteoarthritis in the older population is associated with physical and functional impairment. Recent studies suggest that the impact of the knee osteoarthritis may be reduced with self-management strategies.